ANALYSIS FINANCIAL SERVICES COOPERATION AND THE FACTORS AFFECTING IT VIEWED FROM CUSTOMER PERSPECTIVES - Yurniwati Yurniwati; Zuli Falida Folza; Yessel Pissi (Jurnal Akuntansi, 2020)
Sharia Financial Services Cooperative (KJKS) is a cooperative whose business activities are engaged in financing, investment, and savings under the profit-sharing pattern (sharia). However, the funding provided by KJKS currently has a high risk, thus disrupting the performance of KJKS. The purpose of this study was to analyze the financing of problems in KJKS in the city of Padang. The study was conducted on inefficient KJKS obtained from KJKS which had the lowest increasing return to scale and decreasing return to scale values. The variables studied were non-performing financing (NPF) as the dependent variable and religiosity, financing planning, revenue sharing, initial administration requirements, and KJKS evaluation as an independent variable. The method of analysis uses descriptive analysis and hypothesis test analysis. The results showed the average level of non-performing financing (NPF) KJKS is at high risk, KJKS which has an NPF value above 5% as required by Bank Indonesia. But there are KJKS whose NPF has decreased every year such as the Parak Rumbio and Surau Gadang, Batu Gadang, Ampang, Kurau Pagang domains. Description of the variable of religiosity found the respondents have a good intention to pay the installment financing. The results of hypothesis testing prove that customer religiosity has a significant effect on problem financing. Financing planning does not affect problem financing. Customer income has a significant effect on problem financing. The initial administrative factor does not affect problem financing. The evaluation factor by the KJKS does not affect problem financing. Keyword: Problem Funding; Religiosity; Funding Planning; KJKS